Substitution of Fermented Coffee Skin in Commercial Feed and Addition of Alkaline Water on The Growth of Super Local Chicken - I Dewa Nyoman Sudita; Ni Made Ayu Gemuh Rasa Astiti; Marselina Ngongo Thomas Ngongo Dairo (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2023)
This study aims to determine the effect of using fermented coffee husks as substitute feed and at what level it affects the growth of super-free-range chickens. The research method was carried out using a completely randomized design factorial pattern consisting of 2 factors. The first factor consisted of 3 treatments of fermented coffee skin substitution, namely: K0 = 100% commercial feed, K1 = 95% commercial feed + 5% substitute for fermented coffee skin, K2 = 90% commercial feed + 10% substitute for fermented coffee skin. The second factor consisted of 2 treatments of giving drinking water, namely: A0 = without giving alkaline water, A1 = giving alkaline water with a concentration of 20% in drinking water. The results showed that the substitution of fermented coffee skin on commercial feed had a significant effect on body weight gain in the fifth week. Meanwhile, weight gain at weeks 1, 2, 3, 4, 6, and final weight had no significant effect. Carcass weight and carcass composition had no significant effect but the K1 treatment always gave the highest average. The treatment with alkaline water had no significant effect, the average weight gain was always higher in treatment A1. Based on the results of the study, it can be concluded that the substitution of fermented coffee husks in commercial feed for free-range chicken had a significant effect on body weight gain in the fifth week, but on other variables such as final weight and composition of carcass parts had no significant effect. Meanwhile, the addition of alkaline water and without alkaline water had no significant effect, but the addition of alkaline water had a higher average value for both growth and carcass parts. Substitution of fermented coffee skin on commercial feed as much as 5% showed better results than without substitution and 10% substitution. Keywords: Fermented Coffee Skin, Alkaline Water, super local chicken